Evaluating the effectiveness of using printing equipment - Турчинова, Галина Ивановна; Муравьёва, Елена Валерьевна (Technology audit and production reserves, 2014)
The effectiveness of using printing equipment was studied and the calculations for the qualitative evaluation of the equipment effectiveness in the printing industries were made. The speed and quality of printing depends on the applied printing equipment, for correct using the full capacity of a printing machine, the parameters that affect the performance of the printing equipment were studied (circulation, number of color inks, order format, complexity of orders, number and qualifications of printers). Next, the main parameters (print time, production capacity) were determined that will speed up the printing process, make it more accurate and insure the production from the perpetual violations of order deadline, violations of printing equipment loading schedule. As a result, the printing process will be more organized.